Ensuring the Right of the Child in the Boko Haram Insurgency: The Province of UNICEF’s Complementary Mandate Under International Law - Adegbite, Olusola Babatunde (Indonesian Journal of International Law, 2022)
The need to manage conflict-related humanitarian conditions is the basis of intervention by international humanitarian organizations. Chief amongst these agencies is the United Nations International Children’s Emergency Fund (UNICEF), whose work is primarily about protecting children in armed conflicts. This agency has maintained a robust response to the humanitarian crisis in the Boko Haram insurgency, though its effort has not been without controversies. In 2018, it was suspended by the Nigerian Military on the allegation that it was working for the enemy side, an action which attracted widespread condemnation, as it was seen as an attempt by the government to give the agency a bad name. This has again thrown up the question of whether agencies such as UNICEF have the mandate ascribed to them under international law, and whether countries such as Nigeria, having signed up to this mandate, could refuse to live up to their international obligation. This article examines the framework of humanitarian intervention by UNICEF under international law, and what Nigeria’s role ought to be in this respect. It makes the argument that UNICEF’s intervention in the insurgency is not that of a meddlesome interloper, but part of an international legal framework for the protection of children’s rights in armed conflicts, which Nigeria has signed to, and which it must fulfil. Supporting UNICEF is in the best interest of the country, but doing otherwise could be inimical not just to the wellbeing of children in the insurgency, but also the country’s commitments under international law.